DAMPAK PEMANFAATAN HARTA PUSAKA TINGGI UNTUK PENDIDIKAN DI JORONG SIMPANG AMPEK KABUPATEN PASAMAN BARAT - Santya, Windi; Yuhelna, Yuhelna; Marleni, Marleni (Universitas Tanjungpura, 2022)
High inheritance is a hereditary property from the woman, this property cannot be traded without the consent of the people. However, because there are many pressing things, many people sell this property to meet the needs of their families, one of which is to pay for children's education. However, with the sale of this property, it will have an impact on the family as well as the people. The purpose of this study was to describe the impact of using high inheritance for education in Jorong Simpang Ampek, West Pasaman Regency. The theory used in this study is the theory of Social Change proposed by Herbert Spencer. The research was conducted in Jorong Simpang Ampek, West Pasaman Regency. This study uses qualitative research methods with descriptive research type. The withdrawal of informants was carried out by purposive sampling technique. The data collection method in this study began with observation, in-depth interviews, and document studies.Data analysis was carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that there are 2 impacts of using high heritage assets for education in Jorong Simpang Ampek, West Pasaman Regency including: 1) Positive Impact, for the nuclear family, namely children from people who take advantage of this high inheritance, can go to school to higher education. While the positive impact on the community, mamak feels proud that his nephew has achievements in school so that he can get a higher education.2) Negative impact, for the nuclear family, where at the beginning of the process of selling heirlooms, there are family members who do not agree to be sold then it causes conflict between mamak and other brother. While the negative impact for the people is that the high inheritance which was originally intact becomes reduced and cannot be enjoyed by the next generation.